DAMPAK PELATIHAN PENGUATAN LKM DAN KSM DENGAN MODEL KOMUNIKASI EFEKTIF UNTUK MENINGKATKAN PEMAHAMAN PADA PNPM MP DI KECAMATAN KUDU JOMBANG - Dina Eka Shofiana (Kompetensi (Competence : Journal of Management Studies), 2014)
National Program for Urban Community Empowerment (PNPM MP) is a development model that is being executed ekononomi people to date in various villages throughout Indonesia. PNPM MP who is expected to become the motor of change in the standard of living of the poor into a society that is more powerful and independent, are still not well understood by the offender PNPM MP. To address the lack of understanding of PNPM MP actors, the strengthening of the training given to LKM and KSM to bring in speakers from both government and academia. Strengthening the training program has been oriented towards a model that is considered more effective training can improve the understanding of the perpetrators of PNPM MP in the village called effective communication models. The problems discussed this research are: 1) How effective communication models made in strengthening the training activities of LKM and KSM in the district Kudu ?, 2) What model of effective communication is done in the reinforcement training can improve the understanding of LKM and KSM in PNPM MP in the district Kudu ?. The purpose of this study is to provide a model of discourse need for effective communication to improve understanding of the perpetrators of PNPM MP in village on the nature of PNPM PM. The method used in this research is a field survey with descriptive qualitative data analysis. The results of this study indicate that the model of communications made in strengthening training LKM and KSM have been effective both from the speakers, media, methods, materials and participants as the target audience. Recommendations are given this study is to review the existing training schedule tailored to how materials should be received by LKM and KSM considering training problems is the lack of time allocated